VEHICLE DETECTION USING MILLIMETER WAVE RADAR - POOJA U R; PRAKASH R; KADAR A A (International Journal of Innovations in Engineering Research and Technology, 2021)
ehicle detection has been a vital part of Intelligent Transportation Systems (ITS) for many years, still the vehicle detection method is challenging. Its function is to measure traffic parameters such as flow rate, speed and vehicle types, which are valuable information about road surveillance, traffic signal control, and traffic planning and so on. There are two main types of vehicle detection technologies: intrusive and non-intrusive. Current vehicle detection systems are mainly based on ultrasonic sensors, acoustic sensors, infrared sensors, inductive loops, magnetic sensors, video sensors, laser sensors, and microwave radars. However, ultrasonic, acoustic, and infrared sensors lack stability in noisy environments; inductive loops and magnetic sensors involve disruptive installation process and are prone to damagedue to civil work; the video and laser sensors are usually vulnerable to weather and light conditions, hence not suitable for all-weather working. In comparison, microwave radar systems have high speed-measurement accuracy,